Pengaruh Kebijakan Dividen dan Keputusan Investasi terhadap Nilai Perusahaan dengan Profitabilitas sebagai Variabel Mediasi - Yulia, Yulia; Novalita, Novalita; Sari, Pipit Novila (Universitas Muhammadiyah Metro, 2025)
Using profitability as a mediator, this research seeks to assess the impact of dividend policy and investment decisions on firm value in manufacturing businesses listed on the Indonesia Stock Exchange for the automotive sub-sector from 2021 to 2023. Eleven firms were chosen for the study sample via a purposive selection strategy. Analysis of the data is carried out using SPSS 21's multiple linear regression and path analysis. The findings disprove the hypothesis that dividend policy and investment decisions or profitability. The value and profitability of a company are greatly impacted by investment decisions. A company's worth is positively impacted by its profitability. Nevertheless, there is little evidence that profitability acts as a mediator between dividend policy and investment decisions and business value. Investment choices in the automobile sector directly affect business value, according to these studies. without necessarily going through increased profitability. This research provides insights for managers in optimizing corporate financial strategies and for investors in evaluating key factors in the automotive sector.